Timing of angiography and outcomes in patients with non-ST-segment elevation myocardial infarction: Insights from the evaluation and management of patients with acute chest pain in China registry - Han, Yu; Sun, Shukun; Qiao, Bao; Liu, Han; Zhang, Chuanxin; Wang, Bailu; Wei, Shujian; Chen, Yuguo (Frontiers in Cardiovascular Medicine, 2022)
Objective Although an invasive strategy has been recommended within 24 h for patients with non-ST-segment elevation myocardial infarction (NSTEMI), the optimal timing of the invasive strategy remains controversial. We sought to investigate the association between the different timings of invasive strategies and clinical outcomes in patients with NSTEMI. Materials and methods Patients admitted with NSTEMI from the Evaluation and Management of Patients with Acute ChesT pain in China (EMPACT) registry between January 2016 and September 2017 were included. The primary outcomes were major adverse cardiac events (MACEs) within 30 days. Multivariable logistic regression was performed to assess independent risk factors for MACEs. Results A total of 969 patients with NSTEMI from the EMPACT Registry were eligible for this study. Coronary angiography (CAG) was performed in 501 patients [<24 h, n = 150 (15.5%); ≥ 24 h, n = 351 (36.2%)]. The rate of MACEs at 30 days in all patients was 9.2%, including 54 (5.6%) deaths. Patients who underwent CAG had a lower rate of MACEs and mortality than those who did not receive CAG (MACEs: 5.6% vs. 13.0%, P < 0.001; mortality: 1.6% vs. 9.8%, P < 0.001). Nonetheless, no statistically significant difference was found in the rates of MACEs and mortality between the early (< 24 h) and delayed (≥ 24 h) CAG groups. Older age (OR: 1.036, 95% CI: 1.007, 1.065, P = 0.014), and acute heart failure (OR: 2.431, 95% CI: 1.244, 4.749, P = 0.009) increased the risk of MACEs and protective factors were underwent CAG (OR: 0.427, 95% CI: 0.219, 0.832, P = 0.012) or PCI (OR: 0.376, 95% CI: 0.163, 0.868, P = 0.022). In the multilevel logistic regression, older age (OR: 0.944, 95% CI: 0.932, 0.957, P < 0.001), cardiogenic shock (OR: 0.233, 95% CI: 0.079, 0.629, P = 0.009), pulmonary moist rales (OR: 0.368, 95% CI: 0.197, 0.686, P = 0.002), and prior chronic kidney disease (OR: 0.070, 95% CI: 0.018, 0.273, P < 0.001) was negatively associated with CAG. Conclusion This real-world cohort study of NSTEMI patients confirmed that the early invasive strategy did not reduce the incidence of MACEs and mortality within 30 days compared with the delayed invasive strategy in NSTEMI patients.